Joint Forest Management Heralds a Novel Approach in Kullu - Gupta, S. C. (Indian Forester, 1997)
The JFM was started in Kullu during September, 1994. The staff took an initiative and the JFM Support Team through various participatory training workshops sensitised the field staff as well as local people to bring about an attitudinal change. Nine VFDCs have been formed and six micro plans prepared during last two and half years. The JFM approach has been successful inspite of many apprehensions expressed in the beginning.